Literature Review: Tourist Destinations as Learning Resources for Students to Support Contextual and Meaningful Learning - Nikmatussolihah Nikmatussolihah; I Komang Astina; Tuti Mutia (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study analyzed tourist destinations as learning resources to support contextual and meaningful learning. This qualitative study used the SLR (Systematic Literature Review) model. The Research data were sourced from scientific articles published from 2021 to 2025. Data collection techniques were carried out through searches of Google Scholar, Springer, Emerald, ProQuest, JSTOR, Taylor & Francis, ScienceDirect, and SAGE Journals. The final analysis included 17 journal articles and 2 proceedings. The results showed that tourist destinations play an important role in supporting contextual and meaningful learning. By utilizing tourist destinations, students can relate lesson materials to their surroundings and interact directly with the phenomena and values of the environment. Therefore, students can improve their cognitive knowledge, critical thinking skills, environmental awareness, culture, and local potential. In conclusion, tourist destinations can serve as learning resources, supporting contextual and meaningful learning activities through direct observation and by connecting subject matter to real-life situations. This study suggests that tourist destinations can serve as learning resources, supporting contextual and meaningful learning that strengthens 21st-century skills. This study adds to the literature on meaningful learning and contextual learning for students through learning resources in the form of tourist destinations.